2014
DOI: 10.1186/1471-2458-14-906
|View full text |Cite
|
Sign up to set email alerts
|

Nudging children towards whole wheat bread: a field experiment on the influence of fun bread roll shape on breakfast consumption

Abstract: BackgroundMany children do not eat enough whole grains, which may have negative health consequences. Intervention research is increasingly focusing on nudging as a way to influence food choices by affecting unconscious behavioural processes. The aim of this field study was to examine whether the shape of bread rolls is able to shift children’s bread choices from white to whole wheat during breakfast to increase whole grain intake.MethodsIn a between-subjects experiment conducted at twelve primary schools in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 27 publications
(24 reference statements)
0
24
0
3
Order By: Relevance
“…As such, the present study constitutes a valuable addition to the nudges toolbox to steer children (e.g. Van Kleef, Vrijhof, Polet, Vingerhoeds, & de Wijk, ), adolescents (e.g. Hanks, Just, Smith, & Wansink, ), and adults (e.g.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As such, the present study constitutes a valuable addition to the nudges toolbox to steer children (e.g. Van Kleef, Vrijhof, Polet, Vingerhoeds, & de Wijk, ), adolescents (e.g. Hanks, Just, Smith, & Wansink, ), and adults (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Van Kleef et al, 2012) to better food choices by making small changes to the way food is served or presented. As such, verbal prompts can be considered a type of stimulus control intervention (Van 't Riet, Sijtsema, Dagevos, & De Bruijn, 2011) in which the verbal prompt at the check-out counter serves as the cue and the food choice the (desired) response. As a result of repeated pairing of the cue and the response (associative learning), approaching the check-out counter in and of itself may be a strong enough cue to lead to the same response.…”
Section: Discussionmentioning
confidence: 99%
“…Nudging has recently been studied as a tool to influence healthy food choice by affecting unconscious behavioural processes. Van Kleef, Vrijhof, Polet, Vingerhoeds and de Wijk (2014) provided school children with bread in regular or funny shapes. Their intervention study showed that whole wheat bread consumption doubled when presented as fun-shaped products, demonstrating that visual appeal can stimulate wholegrain consumption.…”
Section: Consumer Perception Of Wholesome Cereal Productsmentioning
confidence: 99%
“…However, is price really a barrier for food choice when it comes to purchasing food for children, given other food industries are effectively marketing high‐priced food items to the children's market? We propose marketing of healthy seafood options, but with a clear focus on making the product more appealing to children by using interesting shapes, natural food dyes, bite‐size portions (e.g., sushi style), and premiums such as small toys or collectibles to encourage repeated consumption (van Kleef, Vrijhof, Polet, Vingerhoeds, & de Wijk, ). Children are attracted to products that have an element of fun, and this may be achieved through novel product development, appealing packaging, and branding.…”
Section: Discussionmentioning
confidence: 99%